The Importance of Oral Language Proficiency in EFL Online Teaching Setting - Flora AMITI (Prizren Social Science Journal, 2020)
English language, as an international language has been used in North Macedonia as a foreign language in schools for a considerable amount of time now. English teachers have tried to convey new ways of teaching this language, furthermore adapting to the main four skills in a meticulous manner.